Application of Integrated Solar-Powered Ultraviolet Radiation and Sand Biofiltration Techniques in Rural Water Treatment: A Review - AWINO, Sindrella; ADEOYE, Peter (FUDMA Journal of Engineering and Technology, 2026)
Access to clean water is still an issue all over the world, and in the context of rural and peri-urban areas of sub-Saharan Africa, it is a matter of grave concern due to widespread contamination of shallow wells and surface water resources by sewage from abattoirs and poultry farms. Commonly available technological solutions for rural water treatment are often very costly, energy-intensive, and technically demanding. This paper reviews the prospects of using sand-based biofiltration (bio-sand filtration) in combination with solar ultraviolet-C (UV-C) disinfection as a multi-barrier engineering solution to access safe water in rural Africa. The basics of sand-based biofiltration, including principles of schmutzdecke formation, pathogen removal kinetics, and hydraulic design are covered together with the basics of photochemical action of UV-C radiation, its dosimetry and limitations due to turbidity. The current state of development of engineering designs was reviewed, particularly the Centre for Affordable Water and Sanitation Technology (CAWST) Version 10 bio sand filter, biologically active carbon media in filters, and sizing solar photovoltaic (PV) power systems to operate UV lamps. Pilot field tests have demonstrated that the technology allows achieving more than 99.99% removal efficiency of bacteria, reduction of turbidity down to 1 NTU, and 40 mJ/cm² irradiance using a 10-16 W lamp and a 100 W PV module. Problems and perspectives of the application of the technology in Uganda with respect to water scarcity, industrial pollution, availability of solar radiation, and appropriate-technology infrastructure are discussed. This paper discusses the potential of Bio-sand filtration (BSF) with solar UV-C disinfection in terms of advancement of Sustainable Development Goal (SDG) 6 in rural Uganda.